PENGARUH FRAUD TRIANGEL DALAM MENDETEKSI FINANCIAL STATEMENT FRAUD - Suri Novira; Yesi Mutia Basri; Pipin Kurnia (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
The aim of this research was to analyze the fraud risk factors of the fraud triangle (pressure, opportunity, and rationalization) in detecting the likelihood of financial statement fraud. The variables of the fraud triangle used are pressure consisting of negative cash flow from operation (NCFO), financial stability (ACHANGE) and external prssure (LEV), the factor opertunity is nature of industry (RECEIVABLE), audit comittee size (ACSIZE) and rationalization are proxied by auditor change (AUDCHENGE). Indication financial statement fraud in this research uses a proxy Beneish M-Score as the dependent variable. The population of this research is the mining company listed in Indonesian Stock Exchange. Total sample was 27 companies the period of 2013 to 2015. Testing the hypothesis used the logistic regression method. The result of this study indicate that only two a factor of pressure consisting of a negative cash flow (NCFO) and financial stability (ACHANGE) effect the financial statements fraud. While other factors are opportunities proxied by the nature of industry (RECEIVABLE), audit committee size (ACSIZE), external prssure (LEV), and rationalization proxied by auditor change (AUDCHANGE) does not affect the financial statement fraud.